O narrador na fronteira entre deixar e apagar marcas: um estudo sobre O matador de Patricia Melo - Pereira, Maria de Fátima da Silva (2005)
We observe in the contemporary novel an increasing lack of narration naturalness that implies in the multiplication of points of view and as a consequence in the narrator s presence inconstancy. Patrícia Melo s novel, O Matador, also shows the instability of this point of view because although the narration is done in first person by the protagonist it doesn t guarantee the constant narrator s presence in the storytelling. This mix between literary and non-literary procedures directly interferes in the narrator s authority because at the time of oral narration the narrator based his story on experience, but currently bases his authority on presentiveness , according to contemporary demand that privileges simultaneity. In this novel the strategies used to obtain presentification of the storytelling have a double consequence: on the one hand they give legitimacy to the facts since they seem to renounce to the narrator s presence and on the other hand they eliminate the protagonist-narrator s traces since at times he behaves as a spectator. Ultimately, the study of this narrator who often oscillates between leaving and eliminating traces, behaving as an observer of the roles played by himself, questions and at the same time reinvents the representation apparatus using the different presentification strategies like advertisements, TV news, newspapers, lack of marks in the change in voice in the dialogues, etc. This attitude will set a fast pace to the story and the apparent lack of mediation will contribute to strengthening a pact with the reader. Therefore in O Matador we observe the dramatization of the loss in the naturalness of telling a story through discourse